The acoustic black hole: A review of theory and applications - Pelat, Adrien; Gautier, François; Conlon, Stephen C.; Semperlotti, Fabio (Journal of sound and vibration, 2020)
The Acoustic Black Hole (ABH) is a technique for passive vibration control that was recently developed within the Structural Dynamics and Vibroacoustics communities. From a general perspective, the ABH effect is achieved by embedding a local inhomogeneity in a thin-walled structure, typically a beam or a plate. This inhomogeneity is characterized by a variation of the geometric properties (although material variations are also possible) according to a spatial power law profile. The combination of a local stiffness reduction, due to the power law variation of the wall thickness, and of a local increase in damping, provided by the concurrent application of viscoelastic layers, gives rise to a significant reduction of the wave speed and to a remarkable enhancement of the attenuation properties. As an elastic wave travels within an ABH, its speed experiences a smooth and continuous decrease. In the ideal case, that is when the wall thickness vanishes at the ABH center, the wave speed decreases to zero. In the non-ideal case, that is when the ABH has a non-zero residual thickness at its center, the wave speed still decreases smoothly but it never vanishes. In this latter case, which is of great importance for practical applications, the ABH is typically combined with lossy media (e.g. viscoelastic layers) in order to achieve significantly enhanced structural loss factors. If the speed of an incoming wave can vanish inside the ABH, it follows that this object behaves as a wave trap that extracts elastic energy from the host medium without, in principle, ever releasing it. Several characteristic properties are generally observed in structures with embedded ABHs: significant reduction in vibration and acoustic radiation levels, low reflection coefficient at the ABH location, localized vibration and trapped modes, and existence of cut-on frequencies. Contrarily to passive vibration methods based on viscoelastic materials, the ABH was developed and applied to reduce vibrations and structure-radiated noise without increasing the total mass of the system. More recently, applications to other areas including elastic metastructures, energy harvesting, vibro-impact systems, and cochlear systems were also investigated. This review is intended to provide a comprehensive summary of the state-of-the-art of ABH technology, spanning from theoretical and numerical contributions to practical applications.